The role of mentoring in promoting diversity equity and inclusion in STEM Education and Research. Issue 1 (17th June 2022) - Marshall, Andrea G; Vue, Zer; Palavicino-Maggio, Caroline B; Neikirk, Kit; Beasley, Heather K; Garza-Lopez, Edgar; Murray, Sandra A; Martinez, Denise; Crabtree, Amber; Conley, Zachary C; Vang, Larry; Davis, Jamaine S; et al.
Abstract: The success of mentoring derives from active and respectful listening and the willingness to learn and accept opportunities for personal growth. This shapes every trainee and their destined path in science, technology, engineering, and mathematics (STEM). The act of cultivating rapport, asking, and pondering meaningful questions, and receiving constructive feedback are critical to support a productive mentoring relationship. Successful mentoring in STEM can be established and allow mentees, especially underrepresented minorities (URMs), to flourish in an environment where they feel welcomed and supported. However, mentees from underrepresented groups often experience inadequate mentoring due to a mentor's lack of awareness, poor trainings themselves, or lack of understanding of the mentee's hardships. It is important for mentors and mentees to work together to promote diversity, equity, and inclusion (DEI) in STEM education through creativity, authenticity, and networking. We analyzed data obtained from students who attended a recent workshop that are interested in going to graduate school. Our results show that despite low initial expectations for the workshop, many students were satisfied in the knowledge they gleaned. The future and role of diversity in STEM within these underrepresented groups lies in community support and an important role that they can play in the lives of others through DEI initiatives and throughout their careers all of which involves positive mentoring. Abstract : Notably, underrepresented minorities (URM) trainees often experience inadequate mentoring due to their mentor's inexperience with URM groups, poor mentorship training, or a lack of understanding of their mentee's journey.